The duration of the board of directors of the associations and the Olympic Game Tokio - Romero Antola, Mario (2021)
The present work analyzes the theme of the Real Estate transfer system in Peru, from the perspective of legal certainty involved in legal transactions, governed by the regulations of the Civil Code in more than 36 years that it has been in force. The article 949° of The Peruvian Civil Code, describes the principle of consent for the development of Real Estate transfer, stating that ¨The sole obligation to dispose a specific property, makes the creditor the owner of it, unless otherwise stipulated or agreed¨. In this sense, the approach of the present work is focused on what legal certainty this system may offer, beyond the work in the field of the transfer system; it also proposes new perspectives that could provide greater legal certainty in Real Estate trade, increasingly growing in our country in recent years.